Use of Respiratory Support in the Biphase Ventilation Airway Mode in the Newborn - S. N. Koval; A. Ye. Kulagin (Общая реаниматология, 2006)
Biphasic positive airway pressure (BIPAP) (also known as DuoPAP, BiLevel, BiVent, PCV+, SPAP) is a mode of ventilation with cycling variations between two continuous positive airway pressure levels. It is a mixture of pressure controlled ventilation and spontaneous breathing, which is unrestricted in each phase of the respiratory cycle. The volume displacement caused by the difference between Phigh and Plow airway pressure level. The phase time ratio (PTR — the BIPAP frequency) is calculated as the ratio between the durations of the two pressure phases, a PTR greater than 1:1 is called APRV (airway pressure release ventilation). In patients with ARDS maintained spontaneous breathing with BIPAP resulted in lower venous admixture and better arterial blood oxygenation as compared with A/C. Only a few studies with BIPAP have been performed in newborn and infants until now. We studied the use of BIPAP in newborn (body mass > 3kg) and randomised 40 patients with respiratory failure for ventilation with BIPAP (n=20) or conventional mechanical ventilatory support (assist-control A/C) — synchronised intermittent mandatory ventilation (SIMV)) (n=20). The Pediatric Risk of Mortality score (PRISM) were collected for each patient. Fentanyl, diazepam, GABA were used as sedatives and adjusted in accordance with the Cook scale. We compared ventilatory parameters, information pertaining to pulmonary function and oxygen delivery, cardiac output, additional descriptors of organ system functions, duration and complications of ventilation and number and dosages of sedatives administered. All the patients that we intended to ventilate with BIPAP were successfully ventilated, we can conclude that biphasic ventilatory support suitable mode of ventilation for newborn with a decreased need of analgetics and sedatives than A/C. Finally, BIPAP is an a effective safe, and easy to use for personal mode of mechanical ventilatory support in newborn.